THE WAYANG GOLEK PERFORMANCE AS ONE OF THE VARIETY OF THE ARTISTS OF THE PUP THAT ARE AVAILABLE ON THE ISLAND OF JAVA - Fauzi, Ratna Puspita; Bahari, Nooryan (Runtas : Journal Of Arts And Culture, 2023)
The Indonesian nation has diverse cultural and ethnic backgrounds. One form of cultural diversity that exists is wayang. The islands of Java and Bali have become places for the development of traditional wayang arts. The UN oversees an institution called UNESCO as an institution that focuses on issues regarding education, culture and science, which then records wayang as a work of cultural art in the international world. By giving this award, the Indonesian people should protect and preserve wayang.This study aims to examine, identify, and know the meaning of cultural traditions and symbols contained in wayang golek performances and their influence on the surrounding community and daily activities. In this study, the method used is the observation method, by collecting data from various sources of journals and the internet, while in analyzing using the phenomenological method.From the research that has been done, it is found that the wayang golek show contains teachings and good values conveyed by a dalang with his characteristics so that the messages to be conveyed can be easily accepted by the public watching the wayang performance. Wayang shows have an impact on several aspects including social, political, economic, and religious aspects.Keywords: Wayang Golek, Symbol, Value